Equações diferenciais parciais lentamente não dissipativas - Sousa, Esaú Alves de (2017)
In thisworkwestudytheasymptoticbehaviorofthesolutionsofpartialdi erential equations slowlynon-dissipative,wewillgiveabriefhistoricaloverviewonthetheme, wewillpresentanintroductiontothetheoryofsemigroupsofboundedlinearoperators in Banachspaces,fractionalpowersofsectoroperatorsandresultsontheexistenceand uniqueness ofsolutionsofabstractCauchysemilinearproblemsoftheparabolictype.